Integrating Religious Moderation into Islamic Religious Education: Strategies and Impacts - Ratnah; Ali Shah, Syed Ahmad; Alam, Mumtaz (At-tadzkir: Islamic Education Journal, 2024)
This study examines the implementation of religious moderation values in Islamic religious education at SMK TI Bali Global Klungkung. Through a qualitative approach, the main finding of this research is the identification of ten religious moderation values being implemented: justice, balance, tolerance, centrism, love for the country, deliberation, improvement, pioneering, non-violence, and cultural friendliness. The implementation is achieved by integrating these values into the curriculum, evaluation techniques, and daily life practices, as well as through habituation and exemplification. The results have positive implications, such as establishing harmonious relationships between Muslim students and the community, increasing student achievement and creativity, and boosting the number of Muslim students in the school. The findings align with the concept of moderation in Islam, behavioristic theory, and expert opinions on religious moderation as a solution to the problem of radicalism. This research contributes to forming students with moderate, tolerant, fair, balanced, and non-violent characters who can adapt to a pluralistic environment following the objectives of Islamic education. The limitation of this study is that its scope is confined to one school.